Humor Affects Fairness Considerations in the Gain and Loss Contexts - Yang, Zhong; Fu, Di; Qi, Yue; Zheng, Ya; Li, Qi; Liu, Xun (Frontiers in Psychology, 2019)
Human decision-making behaviors in social contexts are largely driven by fairness considerations. The dual-process model suggests that in addition to cognitive processes, emotion contributes to economic decision-making. Although humor, as an effective emotional regulation strategy to induce positive emotion, may influence an individual’s emotional state and decision-making behavior, previous studies have not examined how humor modulates fairness-related responses in the gain and loss contexts simultaneously. This study uses the Ultimatum Game (UG) in gain and loss contexts to explore this issue. The results show, in the gain context, viewing humorous pictures compared to humorless pictures increased acceptance rates and this effect was moderated by the offer size. However, we did not find the same effect in the loss context. These findings indicate that humor’s affection for fairness considerations may depend on the context and provide insight into the finite power of humor in human sociality, cooperation and norm compliance.